2023
DOI: 10.3390/foods12183491
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Beneficial Effects of Brazilian Native Fruits and Their By-Products on Human Intestinal Microbiota and Repercussions on Non-Communicable Chronic Diseases—A Review

Maiara da Costa Lima,
Heloísa Maria Almeida do Nascimento,
Jaielison Yandro Pereira da Silva
et al.

Abstract: Non-communicable chronic diseases (NCDs) are the most widespread cause of mortality worldwide. Intestinal microbiota balance can be altered by changes in the abundance and/or diversity of intestinal microbiota, indicating a role of intestinal microbiota in NCD development. This review discusses the findings of in vitro studies, pre-clinical studies and clinical trials on the effects of Brazilian native fruits, their by-products, as well as their bioactive compounds on human intestinal microbiota and NCD. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 126 publications
0
1
0
Order By: Relevance
“…Lima et al [4], through a review paper, showed that Brazilian native fruits, such as acerola, açaí, baru, buriti, guava, jabuticaba, juçara, and passion fruit, and their by-products are rich in bioactive compounds, including soluble and insoluble fiber and a variety of phenolic compounds. The authors gathered information showing that Brazilian native fruits and their by-products can exert beneficial effects on gut microbiota composition with promising repercussions in treating and preventing non-communicable chronic diseases.…”
mentioning
confidence: 99%
“…Lima et al [4], through a review paper, showed that Brazilian native fruits, such as acerola, açaí, baru, buriti, guava, jabuticaba, juçara, and passion fruit, and their by-products are rich in bioactive compounds, including soluble and insoluble fiber and a variety of phenolic compounds. The authors gathered information showing that Brazilian native fruits and their by-products can exert beneficial effects on gut microbiota composition with promising repercussions in treating and preventing non-communicable chronic diseases.…”
mentioning
confidence: 99%